Gen Z Generation's Difficulties in Proving Trigonometric Identities with The Help of Gpt Chat - Putih Fitri; Yusuf Hartono; Meryansumayeka Meryansumayeka (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Artificial Intelligence (AI) and machine learning technologies, which play an important role among emerging technologies, have developed rapidly and have begun to be used in various fields in recent years, especially in education. Many factors cause low student learning ability in mathematics lessons. This study aimed to analyze Gen Z students' difficulties in completing trigonometric identity proofs by utilizing ChatGPT Trigonometry-assisted learning. The type of research used was qualitative research. Research data were collected through observation of student activities, direct interviews, and related literature studies. This research was conducted in SMA N 1 Indralaya Selatan. The instruments used were test question sheets and interview guidelines. The results of this study indicate that Generation Z struggles with basic trigonometry concepts, early solution strategies, and proper algebraic manipulation. In addition, reliance on ChatGPT often reduces students' conceptual understanding of the material. This article recommends learning strategies integrating technology and direct teacher assistance to improve learning effectiveness.